PENGARUH CURRENT RATIO (CR) TERHADAP NET PROFIT MARGIN (NPM) PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR INDUSTRI BARANG KONSUMSI - Ajimat, Ajimat; Novianti, Sal Syabilah; Ramadhani, Annisa Alifa (Fakultas Ekonomi dan Bisnis Islam Institut Pesantren Sunan Drajat Lamongan, 2025)
This study aims to determine the Effect of Current Ratio (CR) on Net Profit Margin (NPM) in Manufacturing Companies in the Consumer Goods Industry Sub-Sector Listed on the Indonesia Stock Exchange for the 2015-2019 Period. The method used in this study is Panel Data Regression Analysis. The population in this study uses the financial statements of Manufacturing Companies in the Consumer Goods Industry Sector Listed on the Indonesia Stock Exchange. The sample in this study is Purposive Sampling. The data analysis techniques used are financial ratio analysis, descriptive statistical analysis, statistical analysis through the EVIEWS calculation stages using EVIEWS version 10. The method used in this study is Panel Data Regression Analysis. Based on the partial test results, it shows that the Current Ratio (CR) has a significant effect on Net Profit Margin (NPM).